Review of traffic control techniques for emergency vehicles - Wan Mohd Hafiz bin Wan Hussin; Marshima Mohd Rosli; Rosmawati Nordin (Institute of Advanced Engineering and Science, 2019)
Traffic control system play an important role to manage traffic congestion on the road especially during peak hours and peak seasons. One of the main challenges is to control the traffic when there are emergency cases at traffic light intersection especially peak hours. This could affect the route for emergency vehicles such as ambulance, fire brigade and police car to reach their destination. Due to the increase of traffic congestion during peak hours and peak seasons in Malaysia, there is a need for further evaluation of traffic control techniques. This paper reviewed and consolidated information on the different types of the existing traffic control system for road traffic management such as Radio Frequency Identification (RFID), wireless sensor network and image processing. This paper analysed and compared on the design, benefits and limitations of each technique. Through the reviews, this paper recommends the best traffic control technique for emergency vehicle that offers low price, low maintenance and can be used in various areas of applications.